The Correlation Between Self-Regulated Learning Strategies in Writing and Senior High School Students’ Writing Performance - Nugraeni, Rosary; Akhiriyah, Suvi (Universitas Nusantara PGRI Kediri, 2025)
The objectives of the research were to identify the components of self-regulated learning (SRL) strategies used by high school students in writing performance and to investigate the correlation between self-regulated learning strategies in writing and students’ writing performance among senior high school students. The study employed a quantitative correlational design, with data collected from 126 tenth-grade students who were selected using convenience sampling. To examine students’ writing strategies, the researchers utilized the Writing Strategies for Self-Regulated Learning Questionnaire (WSSRLQ). The instrument demonstrated a high level of internal consistency, as indicated by Cronbach’s alpha coefficient of 0.895. Descriptive statistical analysis revealed that students primarily employed metacognitive and cognitive strategies at a high level, while social-behavioral and motivational strategies were used to a moderate extent. A very strong positive correlation was found (Spearman’s ρ = .849, p < .01) with motivational strategies showing the strongest correlation among the other components. In conclusion, the findings confirm a very strong and significant correlation between SRL strategies and students’ writing performance, with motivational strategies showing the strongest correlation. These findings highlight the importance of integrating SRL focused instruction into EFL writing pedagogy to improve student engagement, autonomy, and writing proficiency. This result contributes to future academic inquiry by offering a basis for further exploration of SRL strategies in diverse EFL writing contexts.